2018
DOI: 10.1080/13102818.2018.1482233
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D influences the prevalence of non-cutaneous carcinomas after kidney transplantation?

Abstract: Malignancy is a key factor that significantly reduces the graft and patient survival after kidney transplantation. Vitamin D (VD) is gaining attention for its pleiotropy, including neoplasia prevention. The aim of our study was to assess the possible association between de novo non-cutaneous carcinomas (non-cuCa) and the VD status in kidney transplant recipients (KTRs). All patients followed up in our transplant center were included in the study from May 2012 until May 2016. We compared KTRs with non-cuCa to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Observational studies report conflicting results for the association between posttransplant malignancies and VD status [86]. A recent study in our transplant center showed that VD-deficient KTRs had higher prevalence of non-cutaneous cancers [94]. A single center study established beneficial effect from active VD supplementation on post-transplant neoplasia rates [95].…”
Section: Vd Pleiotropy After Kt: Malignanciesmentioning
confidence: 99%
“…Observational studies report conflicting results for the association between posttransplant malignancies and VD status [86]. A recent study in our transplant center showed that VD-deficient KTRs had higher prevalence of non-cutaneous cancers [94]. A single center study established beneficial effect from active VD supplementation on post-transplant neoplasia rates [95].…”
Section: Vd Pleiotropy After Kt: Malignanciesmentioning
confidence: 99%